A large shagreen patch with overlying verrucous epidermal naevus: a curious case of colocalization. (1st March 2019) - Bishnoi, A.; De, D.; Vinay, K.; Vishwajeet, V.; Saikia, U. N.
Abstract: Click here for the corresponding questions to this CME article.